COVID-19 vaccine uptake in Skåne county, Sweden, in relation to individual-level and area-level sociodemographic factors: a register-based cross-sectional analysis - Per-Olof Östergren; Louise Bennet; Jonas Björk; Adam Mitchell; Mahnaz Moghaddassi; Malin Inghammar (BMJ Public Health)
Objectives Better understanding of societal factors associated with COVID-19 vaccination can have important implications for public health policy to increase uptake.Methods This study investigated sociodemographic determinants of COVID-19 vaccine uptake with ≥2 doses vs 0 doses, and ≥3 doses vs 2 doses, among adults (≥18 years) in a general population from Sweden followed from 27 December 2020 (n=1 064 548 at the present cross-section—12 June 12 2022). Associations between individual-level and area-level sociodemographic factors and vaccine uptake were modelled with logistic regression, with average marginal effects and estimated proportion vaccinated subsequently estimated.Results Being vaccinated with ≥2 doses vs 0 doses was positively associated with education (tertiary vs primary, OR 1.5, 95% CI 1.3 to 1.7), household disposable income (Q5 vs Q1, OR 2.3; 95% CI 1.9 to 2.7), comorbidities (≥2 doses vs none, OR 1.9, 95% CI 1.8 to 1.9) and residential area type (affluent socioeconomic conditions vs poor, OR 2.0, 95% CI 1.6 to 2.4). Whereas, being born outside Sweden was associated with a lower uptake (low and middle-income countries vs Swedish born, OR 0.6, 95% CI 0.5 to 0.7). The associations were generally similar when comparing booster vs remaining on only two doses. From these ORs, there were consistent differences in the estimated proportion vaccinated both for ≥2 doses and booster vaccination. Absolute changes in percentage vaccinated between affluent and poor areas were largely similar across individual country of birth, income and education, both for at least two doses and for the booster doses.Conclusions COVID-19 vaccine uptake was associated with higher sociodemographic classifications both at the individual level and area level. The predicted proportion vaccinated increased with more affluent socioeconomic conditions and concurrent increases in individual household income were the strongest indicators. This sociodemographic selection showed consistency with respect to entering (obtaining ≥2 doses) and remaining (obtaining at least one booster dose) in the vaccination programme.